2018
DOI: 10.1007/s00520-018-4594-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chemotherapy-induced nausea and vomiting after high-dose melphalan and stem cell transplantation: review of the evidence and suggestions

Abstract: Introduction High-dose melphalan (HDMel) is the most common conditioning chemotherapy regimen for autologous stem cell transplantation (SCT) in patients affected by multiple myeloma (MM). No consensus exists for the emetogenicity or prophylaxis of chemotherapy-induced nausea and vomiting (CINV) in this regimen. Methods Data on the incidence and efficacy/safety of CINV prophylaxis among patients affected by MM undergoing autologous SCT with the HDMel regimen was extracted from electronic databases and analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…In this setting treatments are intense and elicit a persistent emetic stimulus, given that chemotherapy is generally administered repeatedly over multiple consecutive days [19][20]. Even with a triple NK 1 RA/5-HT 3 RA/DEX regimen with components administered daily, response rates in the aprepitant/fosaprepitant studies are inconsistent [6][7][8]17] and suggest a continued unmet need and opportunity for improved control of CINV, particularly nausea. The results seen in the conditioning phase of our study with NEPA more conveniently administered every-other-day were very encouraging, where a complete response (no emesis and no rescue use) rate of 87% was shown in the overall phase [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting treatments are intense and elicit a persistent emetic stimulus, given that chemotherapy is generally administered repeatedly over multiple consecutive days [19][20]. Even with a triple NK 1 RA/5-HT 3 RA/DEX regimen with components administered daily, response rates in the aprepitant/fosaprepitant studies are inconsistent [6][7][8]17] and suggest a continued unmet need and opportunity for improved control of CINV, particularly nausea. The results seen in the conditioning phase of our study with NEPA more conveniently administered every-other-day were very encouraging, where a complete response (no emesis and no rescue use) rate of 87% was shown in the overall phase [14].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst study designed to explore the antiemetic e cacy of an NK 1 RA regimen during the mobilization phase as well as the conditioning phase during which MD-CT is administered for mobilizing stem cells prior to ASCT. Prior studies have only evaluated aprepitant/fosaprepitant during the conditioning phase [17][18]. The intent of this paper is to present the e cacy and safety of NEPA in preventing CINV associated with the emetogenic MD-CT administered during the mobilization phase of this study.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of side effects, palonosetron has a better safety profile, as it does not cause heart problems, in particular QTc prolongation [ 18 ]. Recently, Tendas et al reviewed the literature for emetogenicity and the efficacy and safety of CINV during ASCT with HDM conditioning, and concluded that the aprepitant-based three-drug regimen should be the regimen of choice for CINV prophylaxis in these patients, although the heterogeneity of the studies examined does not allow definitive conclusions to be drawn [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current standard approach for ASCT in MM patients is to use high-dose MEL (HDM) 200 mg/m 2 except in those aged over 70 and those with kidney failure, for whom a lower dose of HDM is used (140 mg/m 2 ) [ 16 , 24 ]. However, very little information is available about its potential impact on the onset of nausea and vomiting in these patients [ 33 ]. The National Comprehensive Cancer Network (NCCN) guidelines recently included parenteral HDM ≥ 140 mg/m 2 in patients with a high emetic risk, and MEL < 140 mg/m 2 in those with a moderate emetic risk [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study designed to explore the antiemetic efficacy of an NK 1 RA regimen during the mobilization phase as well as the conditioning phase during which multiple day chemotherapy is administered for mobilizing stem cells prior to ASCT. Prior studies have only evaluated aprepitant/fosaprepitant during the conditioning phase [17,18]. The intent of this paper is to present the efficacy and safety of NEPA in preventing CINV associated with the emetogenic multiple drugs administered during the mobilization phase of this study.…”
Section: Introductionmentioning
confidence: 99%